Karakteristik Geoteknik Rencana Lokasi Pembangunan Dermaga Peti Kemas Kota Raha, Sulawesi Tenggara - Minmahddun, Anafi (aspal, 2024)
The characteristics of soil, which are homogeneous or even very different even at short distances, are one of the reasons why it is important to carry out geotechnical investigations for building foundation design to prevent failure or excessive settlement. This research aims to determine the geotechnical characteristics of the container port location plan in Raha City. Deep boring and SPT tests were carried out at 2 points: BH-01 in the wharf area and BH-02 at the access road area to the dock (trestle and causeway). Apart from that, samples were taken from two drilling holes to be tested in the laboratory. Laboratory test results obtained based on the USC classification of all samples were classified as silty sand soil (SM) with low plasticity. The boring results show that the hard soil layers in BH-01 and BH-02 are, respectively, at a depth of 12.5 m and 16.5 m. The allowable bearing capacity (Qa) of round piles with a diameter of 45 cm at a depth of 9 m, 10 m, and 11 m with a safety factor of 4 is respectively 892 kN, 919 kN, and 946 kN for BH-01 and 913 kN, 940 kN, and 968 kN for BH-02. The allowable bearing capacity (Qa) of round piles with a diameter of 50 cm at a depth of 9 m, 10 m, and 11 m with a safety factor of 4 is respectively 1057 kN, 1084 kN, and 1112 kN for BH-01 and 1079 kN, 1106 kN, and 1133 kN for BH-02.